Effects of strength training in fibromyalgia on balance, neuromuscular performance, and symptomatic analysis: a 12-week study protocol - Albuquerque, Maria Luiza L.; Monteiro, Diogo; Alvarez, Marcos C.; Vilarino, Guilherme Torres; Andrade, Alexandro; Neiva, Henrique P. (Frontiers in Neurology, 2023)
Fibromyalgia affects skeletal muscles presenting with muscle stiffness, pain, and fatigue. The exercise practice is well-stabilized and suggested for the reduction of symptoms. However, there are some gaps in the literature related to balance and neuromuscular performance in a strength training protocol. The aim of this study is to structure a protocol to verify the effects of strength training applied over a short period, on balance, neuromuscular performance, and fibromyalgia symptoms. Additionally, we intend to analyze the effects of a short period of cessation of training. Participants will be recruited through flyers, internet advertisements, clinical referrals, health professionals, and email outreach. Volunteers will be randomly assigned to the control group or experimental group. Before the training period, symptoms (Fibromyalgia Impact Questionnaire, Visual Analog Scale), balance (force plate), and neuromuscular performance (medicine ball throw and vertical jump) will be assessed. Participants in the experimental group will perform strength training twice a week (50 min each), on alternate days, for eight weeks (16 sessions). Then, four weeks of detraining will be completed. This training program will be carried out online, using real-time videos, and the participants will be divided into two groups with different schedules. The Borg scale will be used to monitor perceived effort in each session. There is a gap in the literature about exercise prescriptions for fibromyalgia. The supervised online intervention enables a wide range of participation. The strength exercises used (without the use of external materials and/or machines) and load (few repetitions per set) represent a novelty to training programming. Moreover, this training program respects the limitations and individuality of the volunteers, providing exercise adaptations. With positive results, the present protocol could be an easy-to-apply guideline with clear instructions on the details related to exercise prescription. Also, ensure the effectiveness of a low-cost and feasible treatment, especially for fibromyalgia patients.